TECHNOLOGIES FOR USING BORROWED LABOR IN THE ERA OF DIGITALIZATION (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The purpose of the article is to identify the essence of borrowed labor, the tools for its implementation, and the possibilities for its introduction in domestic enterprises. It has been established that for a successfully functioning society, it is important for labor markets to remain inclusive, provide those seeking employment with quality jobs, and offer adequate social protection. This requires the development and implementation of new technologies that lead to the rapid development of atypical forms of employment. HR managers need to modernize management tools so that, on one hand, the staff meets the expectations and needs of employees as much as possible, and on the other hand, aligns with the goals, settings, opportunities, and realities of the company's new business environment. However, HR specialists do not always possess the necessary competencies. It has been proven that since in many companies HR functions belong to those that serve the main process, it is advisable to use alternative forms of employment through the mediation of Professional Employer Organizations (PEOs). PEO is a company that offers outsourcing, leasing, or other staffing solutions, usually for small and medium-sized businesses. They handle services such as payroll processing, employee benefits, personnel management, tax administration, and regulatory compliance. The article identifies the advantages and disadvantages of working with PEOs. Delegating operational HR functions to PEOs does not replace the internal HR team. It is substantiated that in Ukraine, borrowed labor is a developing service. Borrowed labor is understood as a form of atypical employment in which an employee is transferred to the disposal of another employer. The application of borrowed labor occurs within the following schemes: 1) staff leasing; 2) outstaffing; 3) outsourcing; 4) temporary staffing. Borrowed labor is currently an emergency and the only option for quickly filling vacancies. Speed and quality of results are the most significant arguments in favor of using borrowed labor. The functions of Ukrainian organizations are limited only to the employment of workers. A list of additional functions that the Ukrainian market expects from staffing agencies has been identified.
Keywords: borrowed labor, staff leasing, outstaffing, outsourcing, temporary staffing, Professional Employer Organization, staffing agencies, recruiting.